ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS X MAN 1 PARIGI DALAM MEMECAHKAN MASALAH SPtLDV DITINJAU DARI JENIS KELAMIN: Analysis of Mathematical Reasoning Ability of Grade X Students at MAN 1 Parigi in Solving SPtLDV Problems Reviewed from Gender - Chalid, Ziyad; Hadjar, Ibnu; Murdiana, I Nyoman; Rizal, Muh. (Aksioma, 2024)
The purpose of this study is to obtain a description of the mathematical reasoning abilities of grade X students at MAN 1 Parigi in solving SPtLDV problems reviewed from a gender. This type of research is qualitative research. The subjects in this study were two grade X MIPA students at MAN 1 Parigi in the even semester of 2022/2023, consisting of one male student and one female student. Data on students' mathematical reasoning abilities were collected using a mathematical reasoning test on the topic of Systems of Linear Inequalities in Two Variables (SPtLDV) and interviews. Based on the analysis obtained, male subjects structured their mathematical problem-solving by using graphs and systems of inequalities to depict the solution area and achieve maximum parking lot revenue. The proof construction by male subjects was more comprehensive in identifying variables, inequalities, and critical points, thus leading to accurate conclusions based on the presentation and arrangement of evidence. Female subjects presented their answers concisely using a system of linear equations without accompanying graphs or verification of extreme points, resulting in less optimal proof construction, which led to less valid conclusions and did not support the objective of the problem effectively. The conclusion from this study is that the mathematical reasoning ability of Class X students at MAN 1 Parigi in solving SPtLDV problems reviewed from a gender perspective, showed that male subjects excelled in mathematical reasoning capabilities compared to female subjects.